The Typology of Religious Thought in Muhammadiyah - Palahuddin, Palahuddin (Universitas Ahmad Dahlan, 2020)
In the perspective of religious thought, Muhammadiyah is often seen as an ambiguous Islamic mass organization. For example, in matters of worship, Muhammadiyah is very consistent in using the Bayani approach in understanding religious texts, but to determine the beginning of the lunar month associated with a time of worship, Muhammadiyah tends to use the Burhani approach. As a consequence, Muhammadiyah is often considered conservative, but at the same time also considered liberal. This perception does not arise if the methodology of religious thought in Muhammadiyah is comprehensively understood. Therefore, this study assessed the typological thinking in Muhammadiyah. A qualitative method was used for describing the characteristics of an individual, circumstances, symptoms, or certain groups based on the phenomenon of the problem reviewed in a comprehensive and depth way. There are three typologies of religious thought in Muhammadiyah, namely conservative typology, liberal typology, and moderate typology.